Pelatihan Pembukuan Sederhana Bagi Ibu-Ibu PKK RT 10 Kelurahan Soe Produsen Keripik Alpukat - Kevin Aditia Gata Koe Totomone, Mikhael; Luis Da Costa, Stefanus; Perdona Hayon, Rosadalima; Barek Maran, Maria; Elsa Nggetu, Theresia; Sonya Mau, Indriwati; Helvinsis Aria Kandil, Vinsensia; Buanarini Thalo , Avrilli; Aprilia Jesandra Densi , Fransiska; Salvator Naitili, Hendrikus; Aldorius Mboi, Yohanes; Kofi, Ignasius; Faren Nomirvan Cawa, Yorcan; Paulus Tinenti, Yeheskial; Ton, Maria; Regina Jaga, Maria (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Simple bookkeeping training activities in the avocado-based chips business are activities carried out to empower the community with existing natural resources in the form of avocados. Thus, existing resources can be made into an MSME product that aims to strengthen the economy of the community. This activity is included in one of the activities of Unwira KKNT-PPM students from the Accounting Study Program. The training aims to help PKK mothers in managing finances and bookkeeping records for the avocado chips business they run. The method used in this training is the delivery of theory and hands-on practice by teaching basic bookkeeping techniques. The result of this training is the increased ability of PKK women in managing finances, make more organized and transparent financial reports, and being able to better monitor the development of their avocado chip business. It is hoped that with this training, the avocado chips business in RT 10 Soe Village can develop and provide benefits to the surrounding community.